Luteolin Exerts Neuroprotection via Modulation of the p62/Keap1/Nrf2 Pathway in Intracerebral Hemorrhage - Tan, Xin; Yang, Yi; Xu, Jianguo; Zhang, Peng; Deng, Ruming; Mao, Yiguang; He, Jia; Chen, Yibin; Zhang, Yan; Ding, Jiasheng; Li, Haiying; Shen, Haitao; et al. (Frontiers in Pharmacology, 2020)
Upregulation of neuronal oxidative stress is involved in the progression of secondary brain injury (SBI) following intracerebral hemorrhage (ICH). In this study, we investigated the potential effects and underlying mechanisms of luteolin on ICH-induced SBI. Autologous blood and oxyhemoglobin (OxyHb) were used to establish in vivo and in vitro models of ICH, respectively. Luteolin treatment effectively alleviated brain edema and ameliorated neurobehavioral dysfunction and memory loss in vivo. Also, in vivo, we found that luteolin promoted the activation of the sequestosome 1 (p62)/kelch‐like ECH‐associated protein 1 (Keap1)/Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway by enhancing autophagy and increasing the translocation of Nrf2 to the nucleus. Meanwhile, luteolin inhibited the ubiquitination of Nrf2 and increased the expression levels of downstream antioxidant proteins, such as heme oxygenase-1 (HO-1) and NADPH: quinine oxidoreductase 1 (NQO1). This effect of luteolin was also confirmed in vitro, which was reversed by the autophagy inhibitor, chloroquine (CQ). Additionally, we found that luteolin inhibited the production of neuronal mitochondrial superoxides and alleviated neuronal mitochondrial injury in vitro, as indicated via tetrachloro-tetraethylbenzimidazol carbocyanine-iodide (JC-1) staining and mitochondrial superoxide (MitoSOX) staining. Taken together, our findings demonstrate that luteolin enhances autophagy and anti-oxidative processes in both in vivo and in vitro models of ICH, and that activation of the p62-keap1-Nrf2 pathway, is involved in such luteolin-induced neuroprotection. Hence, luteolin may represent a promising candidate for the treatment of ICH-induced SBI.